The Influence of Infrastructure, Work Environment, Discipline and Motivation in Improving the Performance of Junior High School Teachers: Pengaruh Sarana Prasarana, Lingkungan Kerja, Disiplin serta Motivasi dalam Meningkatkan Kinerja Guru Sekolah Menegah Pertama - Aliwarno Aliwarno; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2021)
This Research Aims To Determine The Effect Of Infrastructure, Work Environment, Discipline, And Motivation In Improving Teacher Performance At SMP Muhammadiyah 5 Tulangan. The hypothesis in this study is that there is an effect of infrastructure, work environment, discipline, and motivation in improving teacher performance partially and simultaneously. To Test This Hypothesis, Data Hypothesis Tool Is Used In The Form Of Multiple Linear Regression. This research design uses the method of collecting sample data through questionnaires. The sample is all teachers of SMP Muhammadiyah 5 Reinforcement. The Data Collected Then Analyzed With Multiple Regression Analysis Using SPSS Version 21. The Sampling Technique In This Research Is Census. The Research Results Obtained Based On The Validity And Reliability Test Show All Questions On The Questionnaire Are Valid And Reliable. The F test results show that the independent variable has a simultaneous effect on the dependent variable. The T test shows that there is a partial effect between infrastructure, work environment, discipline, and motivation on performance. The results of the determination test state that the variables of infrastructure, work environment, discipline, and motivation have a significant and positive effect on improving teacher performance at SMP Muhammadiyah 5 Reinforcement.